Diamond studies for applications in quantum technologies - Segura, Charlie Oscar Oncebay (2019)
Among several hundred impurities and defects that can occur in diamond, the nitrogenvacancy (NV) center is one of the most interesting for quantum technologies at room temperature. Several properties make it an excellent platform for many applications, from nanosensor to quantum information processing. This thesis presents the first explorations of NV-based technologies in our laboratory, investigating three sets of studies aimed at learning the know-how of this field of research and developing the necessary infrastructure to explore them in future quantum technologies. The first set of studies focus on magnetometry and how to improve NV-based magnetic sensing. We show that, using engineered ensembles of NV centers in ultrapure synthetic diamonds, one can build a relatively simple apparatus to do magnetic imaging of relatively large areas while determining the full vector field with high spatial resolution and very good sensitivity. We also show that these measurements can be used to reconstruct the current density distribution of nearby sources, opening exciting possibilities to study two-dimensional materials. Another set of studies involve spin coherence of an ensemble of NV centers. For that, we developed a method based on a CCD camera and an imaging protocol that allows implementing pulse sequences like Rabi, Ramsey and Hahn echo, performing Electron Spin Resonance (ESR) spectroscopy over extended areas. Using this method we extract parameters from our sample, including measurements for T1, T2 and T*2. The method was also used to observe Electron Spin Echo Envelope Modulation (ESEEM), due to hyperfine interaction with nearby 15N nucleus, resulting in improved frequency sensitivity. The third set of studies explore how to use femtosecond lasers to produce NV centers in diamond and investigated the nonlinear index of refraction (n2) of the diamond (type IIa) in a broad spectral region, from the infrared (1500 nm) to the ultraviolet (260 nm).